EVALUATION OF TRADITIONAL MEDICINES II: THE USE OF METABOLITE PEAK-KINETICS - Makhotso Lekhooa, Makhotso; Walubo, Andrew; Du Plessis, Jan JB; Matsabisa, Motlalepula G; Molefe, Duduzile (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
PHELA is a herbal mixture of four African traditional medicinal plants that is under development by the Medical Research Council (MRC) for use as an immune stimulant in immune compromised individuals. Before major in vivo investigations could be conducted, there was a need to establish a plasma marker for concentration monitoring of PHELA. Chromatographic separation was achieved using a C18 RP column (250 mm x 4.6 mm x 5 µm), 70% acetonitrile in water and fluorescent detection. Three groups of rats (n=5) were administered with PHELA (15.4 mg/kg) and one rat from each group was sacrificed at 1, 2, 4, 6 and 8 hours. Surprisingly, on the HPLC analysis, none of the marker peaks of spiked plasma were detectable in the plasma of treated animals. Instead, a new peak was observed at 9.2 minutes, which implied that it was a metabolite of PHELA. Using peak area per unit plasma volume (PK-area/L), the relevant pharmacokinetic parameters were derived. The metabolite’s half-life was 3.47±0.35 hours and reached maximum concentration at 4.67 ± 1.15 hrs. It was estimated that with once daily dosing of PHELA, the concentration at steady state (Css) would be 47.52 ± 5.94 PK-area/L with no drug accumulation (Acc index =.009 ± 0.004). In conclusion, the use of peak area per unit volume to derive pharmacokinetics of unknown compounds (Peak-kinetics) and to confirm ingestion of PHELA were demonstrated with a hope that they may appeal to those experiencing similar problems with monitoring of herbal products of which little is known.